Housing voices: using theatre and film to engage people in later life housing and health conversations. Issue 4 (5th December 2019) - Bailey, Cathy; Forster, Natalie; Douglas, Barbara; Webster Saaremets, Claire; Salamon, Esther
Abstract : Purpose: Quality, accessible and appropriate housing is key to older people's ability to live independently. The purpose of this paper is to understand older people's housing aspirations and whether these are currently being met. Evidence suggests one in five households occupied by older people in England does not meet the standard of a decent home. The Building Research Establishment has calculated that poor housing costs the English National Health Service £1, 4bn annually (Roys et al., 2016 ). Design/methodology/approach: This paper reports on the findings of a participatory theatre approach to engaging with those not often heard from – notably, those ageing without children and older people with primary responsibility for ageing relatives – about planning for housing decisions in later life. The project was led by an older people's forum, Elders Council, with Skimstone Arts organisation and Northumbria University, in the north east of England. Findings: Findings suggest there is an urgent need to listen to and engage with people about their later life housing aspirations. There is also a need to use this evidence to inform housing, health and social care policy makers, practitioners, service commissioners and providers and product and service designers, to encourage older people to become informed and plan ahead. Research limitations/implications: Use of a participatory theatre approach facilitated people to explore their own decision making and identify the types of information and support they need to make critical decisions about their housing in later life. Such insights can generate evidence for future housing, social care and health needs. Findings endorse the recent Communities and Local Government (2018) Select Committee Inquiry and report on Housing for Older People and the need for a national strategy for older people's housing. Originality/value: Although this call is evidenced through an English national case study, from within the context of global population ageing, it has international relevance.